Exploring the Perceived Success of a Strategic Medical Tourism Alliance Project from the Patients’ Perspective - Xizi Zhang; William P. Wall; Kate Hughes (AIBPM Publisher, 2018)
This paper examines the customer experience of a medical tourism alliance project between a Chinese and a Thai medical hospital. The purpose of the paper is to evaluate the perceived value of this strategic project from the perspective of patients. Qualitative data was collected through a series of interviews with Chinese patients while in Thailand receiving medical treatment, and from the perspective of informed experts. Additional secondary data were collected from reports available from the hospitals, business media, and scholarly publications. This paper explores the voice of the customer as an indicator of post-project success. Keywords – Project Management, Medical Tourism, Voice of the Customer, Strategic Alliance